Grapeleaf Skeletonizer, Harrisina americana (Guerin-Meneville) (Insecta: Lepidoptera: Zygaenidae) - Frank W. Mead; Susan E. Webb (EDIS)
This species is common throughout Florida, with the possible exception of the Keys, and it ranges widely in the eastern half of the United States. It is noticed primarily because of its defoliation of grapevines in home gardens. This document is EENY-191 (originally published as DPI Entomology Circular 92), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 2001.